Gender differences in cephalometric angular measurements between boys and girls - Helsa Alyayuan; Johan Arief Budiman (Dental Journal, 2022)
Background: Gender determination is an important aspect of human biologic profile identification. The human skull is part of the body that has many gender indicators. Lateral cephalogram is used for human skull analysis because of its morphological biologic details, including gender. Purpose: The objective of this study was to determine the difference of angular measurements, those are sella-nasion-point A (SNA), sella-nasion-point B (SNB), point A-nasion-point B (ANB), gonial, mandibular plane, glabella-metopion and sella-nasion (GM-SN), glabella-metopion and Frankfort horizontal plane (GM-FHP), and glabella-metopion and basion-nasion (GM-BaN) angles measurement’s results between boys and girls aged 8-12 years. Methods: This study was an observational analytic on cephalometric radiographs in children aged 8-12 years from July-December 2018 using 54 samples from the Faculty of Dentistry Universitas Trisakti’s Oral and Dental Hospital Radiology Installation. Landmarks determination and angular measurement were digitized. The data were analyzed to a univariate test followed by a statistical test using the independent t-test. Results: The independent t-test showed there are no differences between boys’ and girls’ angular measurement results (p > 0.05). Conclusion: There are no differences in the angular measurements results between boys and girls aged 8-12 years.